Bobsleigh optimization - A customized dynamic vibration absorber with limit stops - Arnold, P.; Glocker, C. (ENOC, 2011)
This paper presents a dynamic vibration absorber for a bobsleigh, that is based on vibration measuring runs on a real track. Observed chassis resonances are reduced by means of an absorber with the assumption that smaller vibration amplitudes should enhance the performance and controllability of the bobsleigh. The device features unconventional elements such as dry friction damping or limit stops for the tuned mass.